The Influence Of Consumer Behavior Factors On Purchasing Decisions At Quinsha Bakery, Gunungsitoli - Larosa, Sri Nibenia; Zebua, Serniati; Zai, Kurniawan Sarototonafo; Harefa, Idarni (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the influence of consumer behavior factors—including cultural, social, personal, and psychological aspects—on purchasing decisions at Quinsha Bakery Gunungsitoli. The problem addressed in this research stems from increasing business competition in the bakery industry, which demands a deeper understanding of consumer behavior. This quantitative research involved data collection through questionnaires distributed to 96 respondents. Data were analyzed using multiple linear regression with SPSS version 27. The results indicate that all four consumer behavior factors have a significant influence on purchasing decisions when tested simultaneously. However, partially, only social and personal factors have a significant impact on purchasing decisions. Cultural and psychological factors do not show a significant individual influence. These findings suggest that marketing strategies should focus more on social and personal approaches, such as lifestyle, social status, and occupation. The study concludes that identifying dominant consumer behavior factors is essential for developing effective marketing strategies and maintaining customer loyalty.